2021
DOI: 10.3390/plants10061088
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping of Salinity Tolerance at the Seedling Stage in a Panel of Vietnamese Landraces Reveals New Valuable QTLs for Salinity Stress Tolerance Breeding in Rice

Abstract: Rice tolerance to salinity stress involves diverse and complementary mechanisms, such as the regulation of genome expression, activation of specific ion-transport systems to manage excess sodium at the cell or plant level, and anatomical changes that avoid sodium penetration into the inner tissues of the plant. These complementary mechanisms can act synergistically to improve salinity tolerance in the plant, which is then interesting in breeding programs to pyramidize complementary QTLs (quantitative trait loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 111 publications
2
17
0
Order By: Relevance
“…Northern Vietnam plays a significant role in these regions due to the vast genetic diversity resulting from its geographic situation and climate (varying from tropical conditions in the Red River Delta lowlands to subtropical climate conditions in the northeast highlands), the presence of many ethnic groups, and over 4000 years of rice cultivation experience [ 10 ]. Despite the abundant genetic resources, a few reports have been published relating to Vietnamese rice landraces with traits of interest, such as flowering time [ 11 ], drought tolerance [ 12 ], and salinity tolerance [ 13 ]. Recently, the resequencing of 672 native rice accessions was performed to explore genetic diversity and trait associations using the genome-wide association study (GWAS) approach [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Northern Vietnam plays a significant role in these regions due to the vast genetic diversity resulting from its geographic situation and climate (varying from tropical conditions in the Red River Delta lowlands to subtropical climate conditions in the northeast highlands), the presence of many ethnic groups, and over 4000 years of rice cultivation experience [ 10 ]. Despite the abundant genetic resources, a few reports have been published relating to Vietnamese rice landraces with traits of interest, such as flowering time [ 11 ], drought tolerance [ 12 ], and salinity tolerance [ 13 ]. Recently, the resequencing of 672 native rice accessions was performed to explore genetic diversity and trait associations using the genome-wide association study (GWAS) approach [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of high-throughput techniques has been employed such as expression reads by RNA-Seq, random and targeted mutagenesis, gene shifting, complementation, and synthetic promoter trapping approaches make many avenues for functional analyses of AbS responsive genes and tolerance mechanisms [ 77 ]. Transcription factors (TFs) are crucially important in knowing the appropriate molecular processes and pathways that are involved in plant growth and survival under AbS conditions [ 78 , 79 , 80 ]. AbS are the quantitative and multiple genes associated in nature, these stress molecular cross-talks and their pathway interconnections are found under AbS conditions.…”
Section: Bioinformatics and Functional Omics Approach To Explore The Abs Tolerance Mechanismmentioning
confidence: 99%
“…Similarly, some of the siRNAs play an important role as stress-inducers and affect protein synthesis including alternative splicing. The genome-wide association studies (GWAS) have become popular to provide novel strategies to identify and characterize the unique stress-responsive genes, which are introduced into crop plants and used in building up the tolerance against various AbS conditions [ 80 ]. In this record, the identification, and characterization of specific stress-responsive genes along with their promoters are analyzed for specificity.…”
Section: Bioinformatics and Functional Omics Approach To Explore The Abs Tolerance Mechanismmentioning
confidence: 99%
“…These studies showed that there were some genes expected to be involved in salt resistance in rice, including a nitrate transporter gene OsNRT2.1 [ 97 ], a MADS-box family transcription factor gene OsMADS31 [ 94 ], a sucrose transport protein gene OsSUT1 , a transcript factor gene OsGAMYB , and some function gene s OsCTR3 , OsMYB6 and OsHKT1;4 [ 88 ], etc. With the development of variety resequencing, salt tolerance GWAS has rapidly developed [ 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. GWAS has exploited the natural variation in root architecture remodeling under salt tolerance to uncover the genetic controls underlying plant responses [ 83 , 106 ].…”
Section: Association Analysis Of Rice Salt Tolerancementioning
confidence: 99%